The Strength of Land Purchase Receipt Evidence: Analysis of Decision Number 334/Pdt.G/2025/PN Pbr - Fransiska Litania Ea Tawa Ajo; Tjempaka Tjempaka (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, in Indonesia’s land law system, every transfer of land rights must be proven by an authentic deed made by a Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT) as a requirement for legal certainty and land rights registration. However, in reality, in judicial practice, land sale and purchase transactions are still often proven merely by simple receipts that do not meet the requirements of an authentic deed as regulated under land law. This study finds that in juridical reality, receipts for land sale and purchase are positioned by judges as private deeds with imperfect evidentiary strength. In accordance with Article 1878 of the Indonesian Civil Code in conjunction with Article 291 of the RBg, such receipts are only binding upon the parties who make them and are not binding on third parties. Nevertheless, judges still accept receipts as valid written evidence; however, receipts cannot stand alone as primary evidence without being supported by other evidence such as witness testimony. Judges determine that land sale and purchase is materially valid if it fulfills Article 1320 of the Civil Code as well as the principles of publicity (open), cash (immediate payment), and real transfer. This decision is conditionally progressive because, although it protects good faith buyers in the contractual aspect, receipts cannot replace the function of PPAT deeds as an absolute requirement for land registration. After the decision, PPATs are required to apply the principle of prudence.